Alfonso Llano SJ: Incitement and Institutional Recovery of the Fields of Medical Ethics and Bioethics in Latin America (Revista Iberoamericana de Bioética, 2019)
Known as one of the founders of Ibero-American Bioethics, Alfonso Llano is a prominent figure within the discipline. In this paper, some of his life events are explained in the pursuit of better understanding his character. His influence is also contextualized in the meaning of his life’s history as a tribute to his legacy. Comparisons with episodes of the intellectual record of the Catholicism are narrated.
Keywords: founders of bioethics; Alfonso Llano; Ibero-American bioethics